Changes in Nkx2.1, Sox2, Bmp4, and Bmp16 expression underlying the lung‐to‐gas bladder evolutionary transition in ray‐finned fishes. Issue 5 (28th September 2020) - Funk, Emily C.; Breen, Catriona; Sanketi, Bhargav D.; Kurpios, Natasza; McCune, Amy
Abstract: The key to understanding the evolutionary origin and modification of phenotypic traits is revealing the responsible underlying developmental genetic mechanisms. An important organismal trait of ray‐finned fishes is the gas bladder, an air‐filled organ that, in most fishes, functions for buoyancy control, and is homologous to the lungs of lobe‐finned fishes. The critical morphological difference between lungs and gas bladders, which otherwise share many characteristics, is the general direction of budding during development. Lungs bud ventrally and the gas bladder buds dorsally from the anterior foregut. We investigated the genetic underpinnings of this ventral‐to‐dorsal shift in budding direction by studying the expression patterns of known lung genes ( Nkx2.1, Sox2, and Bmp4 ) during the development of lungs or gas bladder in three fishes: bichir, bowfin, and zebrafish. Nkx2.1 and Sox2 show reciprocal dorsoventral expression patterns during tetrapod lung development and are important regulators of lung budding; their expression during bichir lung development is conserved. Surprisingly, we find during gas bladder development, Nkx2.1 and Sox2 expression are inconsistent with the hypothesis that they regulate the direction of gas bladder budding. Bmp4 is expressed ventrally during lung development in bichir, akin to the pattern during mouse lung development. During gas bladder development, Bmp4 is not expressed. However, Bmp16, a paralogue of Bmp4, is expressed dorsally in the developing gas bladder of bowfin. Bmp16 is present in the known genomes of Actinopteri (ray‐finned fishes excluding bichir) but absent from mammalian genomes. We hypothesize that Bmp16 was recruited to regulate gas bladder development in the Actinopteri in place of Bmp4 . Graphical abstract: Bmp‐signaling shows an inverted expression pattern along the dorsoventral axis in lung versus gas bladder development. During lung development in bichir, Bmp4 is expressed ventrally in the lung buds, similar to the pattern observed in mouse. Whereas, during gas bladder development in bowfin, Bmp16, a paralog of Bmp4, is expressed dorsally in the gas bladder bud. fg, foregut; GB, gas bladder; L, lung Research Highlight: Ventrally budding lungs and the dorsally budding gas bladder of vertebrates are homologous organs. Paralleling this morphological inversion, paralogous genes, Bmp4 and Bmp16, show an inverted expression pattern during organ developmental outgrowth.